Primary, secondary and compensated male biochemical hypogonadism in people living with HIV (PLWH): relevance of sex hormone-binding globulin (SHBG) measurement and comparison between liquid chromatography-tandem mass spectrometry (LC-MS/MS) and chemiluminescent immunoassay for sex steroids assay. (31st December 2022) - De Vincentis, Sara; Decaroli, Maria Chiara; Fanelli, Flaminia; Diazzi, Chiara; Mezzullo, Marco; Tartaro, Giulia; Tagliavini, Simonetta; De Santis, Maria Cristina; Roli, Laura; Milic, Jovana; Trenti, Tommaso; Pagotto, Uberto; et al.
Abstract: Background: Data about classification of hypogonadism and estrogen deficiency in male people living with HIV (PLWH) are scanty. Aim: To investigate the prevalence and characterization of biochemical hypogonadism and relative estrogen deficiency in male PLWH aged < 50 comparing liquid chromatography-tandem mass spectrometry (LC-MS/MS) with chemiluminescent immunoassay (CI), and combining gonadotropin, sex hormone-binding globulin (SHBG) and serum estradiol (E2) measurements. Methods: Prospective, cross-sectional, observational study. Serum total testosterone (TT), E2, gonadotropins, SHBG were measured by CI. TT and E2 were also assessed by LC-MS/MS. Free testosterone (cFT) was calculated by Vermeulen equation. Results: A total of 316 PLWH (45.3 ± 5.3 years) were enrolled. TT and cFT by LC-MS/MS were lower compared to CI ( p  < 0.0001). The prevalence of biochemical hypogonadism was higher with LC-MS/MS than CI, both for TT (5.1% vs 3.2%, p  < 0.0001) or cFT (9.5% vs 7%, p  < 0.0001). The prevalence of hypogonadism (overt + compensated) was 17.1% for cFT using LC-MS/MS. Secondary form of hypogonadism was more prevalent than primary. The prevalence of relative estrogen deficiency was of 30.0% among hypogonadal patients and 15.5% among eugonadal. Conclusions: The prevalence of male hypogonadism results underestimated by CI compared to LC-MS/MS in PLWH, both for TT and cFT. SHBG and gonadotropins are essential for detecting T deficiency.